2009
DOI: 10.1128/jb.01171-08
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Reduction of the Thermodynamically Less Favorable Electron Acceptor, Sulfate, by a Nitrate-Reducing Strain of the Sulfate-Reducing Bacterium Desulfovibrio desulfuricans 27774

Abstract: Desulfovibrio desulfuricans strain 27774 is one of a relative small group of sulfate-reducing bacteria that can also grow with nitrate as an alternative electron acceptor, but how nitrate reduction is regulated in any sulfate-reducing bacterium is controversial. Strain 27774 grew more rapidly and to higher yields of biomass with nitrate than with sulfate or nitrite as the only electron acceptor. In the presence of both sulfate and nitrate, sulfate was used preferentially, even when cultures were continuously g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 43 publications
4
57
0
7
Order By: Relevance
“…In this study, we found that the activity of nitrate reductase was equivalent in D. desulfuricans grown in the presence or in the absence of Autocolor paint. In the literature, there is little agreement concerning how nitrate reduction is regulated in sulphate-reducing bacteria, even in the well-studied Desulfovibrio genus (Marietou et al 2009;Tarasova et al 2009). Nitrate reductase genes are found only in some sulphate-reducing bacteria and various pathways of nitrate reduction regulation have been described (Marietou et al 2009;Tarasova et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we found that the activity of nitrate reductase was equivalent in D. desulfuricans grown in the presence or in the absence of Autocolor paint. In the literature, there is little agreement concerning how nitrate reduction is regulated in sulphate-reducing bacteria, even in the well-studied Desulfovibrio genus (Marietou et al 2009;Tarasova et al 2009). Nitrate reductase genes are found only in some sulphate-reducing bacteria and various pathways of nitrate reduction regulation have been described (Marietou et al 2009;Tarasova et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is little agreement concerning how nitrate reduction is regulated in sulphate-reducing bacteria, even in the well-studied Desulfovibrio genus (Marietou et al 2009;Tarasova et al 2009). Nitrate reductase genes are found only in some sulphate-reducing bacteria and various pathways of nitrate reduction regulation have been described (Marietou et al 2009;Tarasova et al 2009). In our experiments, we use a modified DSMZ 63 medium containing only half the normal concentration of sulphate, because four Desulfovibrio strains were reported to have constitutive nitrate reductase activity in media containing low concentrations of sulphate (Marietou et al 2009;Tarasova et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations